Pure non-gestational ovarian choriocarcinoma - Mutua Irene; Moses Njoroge; Dennis Inyangala; Mwende Caroline; Denver Mariga; Wairimu Waweru; Swaleh Shahbal; Peter Mwika; Kihiko Kuria; Francis Osawa; Joel Lessan (Elsevier, 2019)
We present a case of a 9-year-old female child who we are managing for pure non-gestational ovarian choriocarcinoma at Kenyatta National Hospital. It is an extremely rare germ cell tumor and quite aggressive. Sub-total hysterectomy, bilateral salpingo-oophorectomy, partial omentectomy and appendicectomy was done. The child is currently undergoing adjuvant chemotherapy. Prognosis is however reported to be dismal. Keywords: Pure non-gestational ovarian choriocarcinoma, Germ cell tumor, Chemotherapy